Mitochondrial Targeted Coenzyme Q, Superoxide, and Fuel Selectivity in Endothelial Cells - Fink, Brian D.; O'Malley, Yunxia; Dake, Brian L.; Ross, Nicolette C.; Prisinzano, Thomas E.; Sivitz, William I. (PLOS ONE, 2009)
Background Previously, we reported that the “antioxidant” compound “mitoQ” (mitochondrial-targeted ubiquinol/ubiquinone) actually increased superoxide production by bovine aortic endothelial (BAE) cell mitochondria incubated with complex I but not complex II substrates. Methods and Results To further define the site of action of the targeted coenzyme Q compound, we extended these studies to include different substrate and inhibitor conditions. In addition, we assessed the effects of mitoquinone on mitochondrial respiration, measured respiration and mitochondrial membrane potential in intact cells, and tested the intriguing hypothesis that mitoquinone might impart fuel selectivity in intact BAE cells. In mitochondria respiring on differing concentrations of complex I substrates, mitoquinone and rotenone had interactive effects on ROS consistent with redox cycling at multiple sites within complex I. Mitoquinone increased respiration in isolated mitochondria respiring on complex I but not complex II substrates. Mitoquinone also increased oxygen consumption by intact BAE cells. Moreover, when added to intact cells at 50 to 1000 nM, mitoquinone increased glucose oxidation and reduced fat oxidation, at doses that did not alter membrane potential or induce cell toxicity. Although high dose mitoquinone reduced mitochondrial membrane potential, the positively charged mitochondrial-targeted cation, decyltriphenylphosphonium (mitoquinone without the coenzyme Q moiety), decreased membrane potential more than mitoquinone, but did not alter fuel selectivity. Therefore, non-specific effects of the positive charge were not responsible and the quinone moiety is required for altered nutrient selectivity. Conclusions In summary, the interactive effects of mitoquinone and rotenone are consistent with redox cycling at more than one site within complex I. In addition, mitoquinone has substrate dependent effects on mitochondrial respiration, increases repiration by intact cells, and alters fuel selectivity favoring glucose over fatty acid oxidation at the intact cell level.